The Clinical and Biophysical Impacts of Voltage-Current-Frequency (VCF) Therapy Using the eMedica Device in Orthopedic Healing - Dongre, Shailesh B; Foujdar, Abdulrehman Irfan; Rohera, Hemant; Bagde, Lajri; Dhengar, Yogita; Nagpal, Deepak (Journal of Neonatal Surgery, 2025)
Background: Orthopedic disorders such as osteoarthritis, fractures, and soft tissue injuries are prevalent causes of disability and chronic pain. Traditional treatments often offer limited regenerative effects and are either invasive or prolonged. Voltage-Current-Frequency (VCF) therapy via the eMedica device introduces a targeted, electroceutical intervention that may overcome these limitations. Objective: To evaluate the scientific basis, therapeutic mechanisms, and observed clinical outcomes of VCF therapy in orthopedic healing, distinguishing it from conventional electromagnetic therapies such as PEMF. Methods: This study synthesizes findings from cellular biology, bioelectric medicine, and preliminary clinical observations. A comparative analysis was performed between VCF and existing electromagnetic therapies. Mechanistic models of VCF-induced tissue repair and inflammation modulation were also reviewed. Results: VCF therapy modulates cellular membrane potentials, enhances ATP synthesis, and activates tissue-specific repair pathways. Clinical observations report accelerated bone and soft tissue healing, improved joint function, and significant reductions in inflammation and pain in patients using the eMedica device. Conclusion: VCF therapy represents a novel, non-invasive, and biologically targeted approach to orthopedic rehabilitation. Its integration into mainstream clinical practice has the potential to revolutionize musculoskeletal healing, warranting further investigation through controlled clinical trials.